The Deep Sea and Me: Using a Science Center Exhibit to Promote Lasting Public Literacy and Elucidate Public Perception of the Deep Sea - Darr, Katherine D.; East, Jennifer L.; Seabrook, Sarah; Dundas, Steven J.; Thurber, Andrew R. (Frontiers in Marine Science, 2020)
A critical barrier to effective management of deep-sea resources is a lack of understanding by society of the benefits received from the oceans. To address this knowledge gap, we applied an iterative design-based research methodology to evaluate (1) how to effectively use an exhibit to increase public literacy of the deep sea over the short and long-term and (2) how visitors to a public science center perceive the deep sea. Using observations of visitor interactions and surveys of visitors, we evaluated three iterations of an exhibit that highlighted deep-sea ecosystem services and habitats as a case study of exhibit efficacy. Exhibits containing video and interactive components were effective in communicating deep-sea information that was retained by visitors over the long-term. For many visitors, the exhibit was their first introduction to the deep sea. Visitors agreed it is important to learn about the deep sea and expressed interest in learning more about deep-sea animals, habitats, resources, and benefits to humans. Visitors tended to agree with protection-oriented value statements and disagree with use-oriented value statements towards the deep sea. This study provides insight into how to effectively communicate policy-relevant information about the deep sea to an audience that has little to no prior knowledge of the ecosystem, yet who will be increasingly responsible for making use decisions of this habitat.